LONG-TERM VARIABILITY IN THE COURSE OF ICE PHENOMENA ON THE VISTULA RIVER IN TORUŃ - Pawłowski, Bogusław (Bulletin of Geography. Physical Geography Series, 2009)
Our first information of ice cover on the Vistula River in Poland dates from the Middle Ages. However, only since the 19th century have continuous observations been available. This study makes use of a data series, obtained mainly from IMGW (Institute of Meteorology and Water Management), covering the years 1861–2003 for ice phenomena and 1814–2003 for ice cover. Considerable shortening has been observed in the duration of both ice phenomena (from 60–120 days to 30–80 days) and ice cover (from 40–100 days to 20–60 days). These trends correspond well with the trend in winter temperatures becoming warmer. However, the transformation of the ice regime on the Vistula River in Toruń has also been affected by the river control, the construction and operation of the Włocławek Dam and (to a lesser degree than at Korzeniewo) icebreaking activities.